Pengujian Mutu Bihun Instan sebagai Produk dalam Program Pemberian Makanan Tambahan (PMT) untuk Ibu Hamil - Yulizar Verda Febrianto; Nurheni Sri Palupi; Feri Kusnandar (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2017)
. The purpose of Feeding Program for Pregnant Mother are for adding nutritious value in food for pregnant mothers group in order to increase nutritional status and quality of newborn child. The program were conducted by fortifying nutritious substances for examples, vitamin A, folic acid, vitamin C, Ferrum (Fe), Zinc (Zn), and iodium in instant beehoon product. Proximate analysis and analysis of fortified substances are conducted in this experiment. Organoleptic test was done for determining whether there are any differences between unfortified beehoon and fertified beehoon from organoleptic side of view. Result of analysis shown that fortification could improve nutritious value in instant beehoon. Processing step of instant beehoon has decreased several fortificants, as vitamin A, folic acid, and vitamin C were decreased. However, processing also improved FE, Zn and Iodium content in instant beehoon. Result shown in differentiate test between NF beehoon and F was significantly different in 95% of confidence interval. Shelf-life of NF and F beehoon stored in room temperature (25oC) acording to organoleptic test result were 9.94 and 8.07 months. Meanwhile, shelf-life of NF and F beehoon in room temperature (25oC) according to chromameter were 10.74 and 11.68 months.